Caputo Fractional Derivative Hadamard Inequalities for Strongly m-Convex Functions - Xue Feng; Baolin Feng; Ghulam Farid; Sidra Bibi; Qi Xiaoyan; Ze Wu (Journal of Function Spaces)
In this paper, two versions of the Hadamard inequality are obtained by using Caputo fractional derivatives and strongly m-convex functions. The established results will provide refinements of well-known Caputo fractional derivative Hadamard inequalities for m-convex and convex functions. Also, error estimations of Caputo fractional derivative Hadamard inequalities are proved and show that these are better than error estimations already existing in literature.